Constructing Multi-Level Test in Statistics for Level University Grades According To the Three Parameter Model - Olaimat, Mohammad (DIRASAT: EDUCATIONAL SCIENCES, 2016)
Abstract: The research study has been completely exemplified the concept of multi-level tests in statistics for level university grades according to the three parameter model. The concept of this approach defines the use or accessibility of multivariate statistical analysis in examining the university grading system. This complete research study examines the use of multiple statistical tools that enlightens the different level outcomes. The concept of university grading system potentially defines the management criterion in terms of implementing marking system. The results that obtained from this study must provide lucrative outcomes. These outcomes must depict the multi-level statistical approach and use of three parameter models in examining the university grading system.